Efektivitas Tenaga Kependidikan Dalam Pengelolaan Data Akademik di SD Harapan Ummah Karawang - Fera Lorenza; Abu Bakar; Lilis Lilis (Peneliti.net, 2022)
Academic data processing is very important for schools because it can affect the learning process. This needs to be considered by the SDIT Harapan Ummah manager because currently data management is still done manually, namely recording data in the ledger, and reports that are also recorded in the ledger. As a result, problems often occur, including recording errors or data loss because every year there is more and more data so it is very difficult to find old data. For this reason, this research will build an Academic Data Processing Information System that can assist academic data processing, ensure data security, and make reports so that learning activities can run more effectively and efficiently. This research is a qualitative research with a software engineering approach. Collecting data by using observation, interview, documentation, and literature study techniques. With this research method to build an Academic Data Processing Information System that processes registration data, attendance, tuition fees, teachers, and assessment of learning outcomes, as well as reports